The Influence of Motivation on Work Productivity of Makassar Akhwat Sewing House Employees - Hanifa Ardiana; Chalid Imran Musa; Muh. Ikhwan Maulana Haeruddin; Zainal Ruma; Tenri S.P. Dipoatmodjo (International Humanity Advance, Business & Sciences, 2023)
This study aims to examine and analyze the influence of motivation on the productivity of Makassar Akhwat sewing house employees. The source of data in this study is primary data obtained by distributing questionnaires to respondents. The population is 118 employees with a sample of 26 production employees. This study uses a simple linear regression method. T test and coefficient of determination. The results of this study indicate that the variable Work Motivation (X) has a positive and significant effect on Work Productivity (Y). This is shown from the results of the t test obtained by the Work Motivation variable which has a t count > t table and has a significance value that is less than the confidence level of 0.05 or has a t count of 2.520 > t table.